Rating and Ranking the Role of Bibliometrics and Webometrics in Nursing and Midwifery. (6th January 2014) - Davidson, Patricia M.; Newton, Phillip J.; Ferguson, Caleb; Daly, John; Elliott, Doug; Homer, Caroline; Duffield, Christine; Jackson, Debra
Abstract : Background . Bibliometrics are an essential aspect of measuring academic and organizational performance. Aim . This review seeks to describe methods for measuring bibliometrics, identify the strengths and limitations of methodologies, outline strategies for interpretation, summarise evaluation of nursing and midwifery performance, identify implications for metric of evaluation, and specify the implications for nursing and midwifery and implications of social networking for bibliometrics and measures of individual performance. Method . A review of electronic databases CINAHL, Medline, and Scopus was undertaken using search terms such as bibliometrics, nursing, and midwifery. The reference lists of retrieved articles and Internet sources and social media platforms were also examined. Results . A number of well-established, formal ways of assessment have been identified, including h - and c -indices. Changes in publication practices and the use of the Internet have challenged traditional metrics of influence. Moreover, measuring impact beyond citation metrics is an increasing focus, with social media representing newer ways of establishing performance and impact. Conclusions . Even though a number of measures exist, no single bibliometric measure is perfect. Therefore, multiple approaches to evaluation are recommended. However, bibliometric approaches should not be the only measures upon which academic and scholarly performance are evaluated.